A Self-Regulation Model of Sexual Grooming. (January 2017) - Elliott, Ian A.
A preparatory process is widely accepted to be a common feature in the perpetration of sexual offenses. Numerous commentators, however, have documented the difficulties in defining and understanding this process, given its transient nature and its specificity to this one form of criminal behavior. This theoretical review aims to provide a universal model of a grooming process for the achievement of illicit or illegal goals in which achievement requires the compliance or submission of another individual—one that can be applied both to the sexual offending process and beyond. First, an evaluation of three process models of grooming is conducted. Second, using a process of theory knitting, an integrated universal model of illicit grooming is developed. This model unites salient elements of the previous models while seeking to address their limitations. It is founded in control theory and self-regulation approaches to behavior, assumes a goal-directed protagonist, and comprises two distinct phases, namely, (1) a potentiality phase of rapport-building, incentivization, disinhibition, and security-management and (2) a disclosure phase in which goal-relevant information is introduced in a systematic and controlled manner in order to desensitize the target. Finally, the theoretical quality of the model is appraised, and its clinical implications are discussed.